Green cellulose-based adsorbent as an effective PFAS sampling tool - Lim, Kang Brian (Nanyang Technological University, 2023)
The development of efficient, sustainable sorbents with high reusability is a key issue in PFAS removal from water. This project aims to develop an amine-functionalised cellulose adsorbent with magnetic properties to facilitate reusability and enhance adsorption. Increasing amounts of polyethylenimine were grafted onto cellulose nanofibrils to improve the overall surface functionalisation while adding adsorption sites. They were then characterised by elemental analysis, acid base titration, fourier transform infrared (FT-IR) spectroscopy, transmission electron microscopy and scanning electron microscopy to determine the most optimal ratio. Thereafter, silica coated ferrous magnetic nanoparticles are synthesised and functionalised with amine groups to facilitate grafting to the amine-functionalised cellulose product, thus providing the magnetic properties for reuptake.